Produção de bioetanol de segunda geração pelo consórcio Zymomonas mobilis CCT4494 e Candida tropicallis em resíduos de uvas Isabel e Bordô - Furlan, Anelisa Doretto Freitas [UNESP] (2015)
The production of fuel ethanol from lignocellulosic residues, as an emerging technology, known as second-generation bioethanol is being extensive research because of a concern with the development of renewable and cleaner energy sources. In this context, the wine industry has highlighted, since the by-product generated by them, bagasse and stems, for example, is the slow decomposition. While there search for new substrates, there are also micro-organisms capable of fermenting monosaccharides present in these residues to produce bioethanol, and also that they are able to ferment in a consortium without competition between them for better use of these carbon sources . In this work were carried out fermentations by Zymomonas mobilis CCT 4494 bacteria and the yeast Candida tropicalis in hydrolyzed acid waste grape species Isabel and Bordô, for this, we used the sulfuric ...